Optimization of a lentivirus-mediated gene therapy targeting HIV-1 RNA to eliminate HIV-1-infected cells - Amanda B. Buckingham; Sophia Ho; Finlay Knops-Mckim; Carin K. Ingemarsdotter; Andrew M.L. Lever (Elsevier, 2024)
Persistence of HIV-1 in cellular reservoirs results in lifelong infection, with cure achieved only in rare cases through ablation of marrow-derived cells. We report on optimization of an approach that could potentially be aimed at eliminating these reservoirs, hijacking the HIV-1 alternative splicing process to functionalize the herpes simplex virus thymidine kinase (HSVtk)/ganciclovir (GCV) cell suicide system through targeted RNA trans-splicing at the HIV-1 D4 donor site. AUG1-deficient HSVtk therapeutic pre-mRNA was designed to gain an in-frame start codon from HIV-1 tat1. D4-targeting lentiviral vectors were produced and used to transduce HIV-1-expressing cells, where trans-spliced HIV-1 tat/HSVtk mRNA was successfully detected. However, translation of catalytically active HSVtk polypeptides from internal AUGs in HSVtkΔAUG1 caused GCV-mediated cytotoxicity in uninfected cells. Modifying these sites in the D4 opt 2 lentiviral vector effectively mitigated this major off-target effect. Promoter choice was optimized for increased transgene expression. Affinity for HIV-1 RNA predicted in silico correlated with the propensity of opt 2 payloads to induce HIV-1 RNA trans-splicing and killing of HIV-1-expressing cells with no significant effect on uninfected cells. Following latency reversing agent (LRA) optimization and treatment, 45% of lymphocytes in an HIV-1-infected latency model could be eliminated with D4 opt 2/GCV. Further development would be warranted to exploit this approach.